Military deployment's impact on the surgeon's practice. Issue 2 (August 2021) - Hall, Andrew; Qureshi, Iram; Vasquez, Matthew; Iverson, Kyle; Tadlock, Matthew D.; McClendon, Hampton; Davis, Elizabeth; Glaser, Jacob; Hanson, Matthew; Taylor, Jonathan; Gurney, Jennifer M.
Abstract : BACKGROUND: As the United States withdraws from overseas conflicts, general surgeons remain deployed in support of global operations. Surgeons and surgical teams are foundational to combat casualty care; however, currently, there are few casualty producing events. Low surgical volume and acuity can have detrimental effects on surgical readiness for those frequently deployed. The surgical team cycle of deployment involves predeployment training, drawdown of clinical practice, deployment, postdeployment reintegration, and rebuilding of a patient panel. This study aims to assess these effects on typical general surgeon practices. Quantifying the overall impact of deployment may help refine and implement measures to mitigate the effects on skill retention and patient care. METHODS: Surgeon case logs of eligible surgeons deploying between January 1, 2017, and January 1, 2020, were included from participating military treatment facilities. Eligible surgeons were surgeons whose case logs were primarily at a single military treatment facility 26 weeks before and after deployment and whose deployment duration, location, and number of deployed cases were obtainable. RESULTS: Starting 26 weeks prior to deployment, analyzing in 1-week intervals toward deployment time, case count decreased by 4.8% ( p < 0.0001). With each 1-week interval, postdeployment up to the 26-week mark, case count increased by 6% ( p < 0.0001). Cases volumes most prominently drop 3 weeks prior to deployment and do not reach normal levels until approximately 7 weeks postdeployment. Case volumes were similar across service branches. CONCLUSION: There is a significant decrease in the number of cases performed before deployment and increase after return regardless of military branch. The perideployment surgical volume decline should be understood and mitigated appropriately; predeployment training, surgical skill retention, and measures to safely reintegrate surgeons back into their practice should be further developed and implemented. LEVEL OF EVIDENCE: Economic/Decision, Level III. Abstract : Supplemental digital content is available in the text.